PENERAPAN MODEL PEMBELAJARAN CTL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI 005 SIBERAKUN KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Lenawati (PGRI Provinsi Riau, 2021)
This research was conducted using a Contextual Teaching and Learning (CTL) approach to improve the activities and learning outcomes of mathematics for grade VI students of SD NEGERI 005 Siberakun, Benai District, Kuantan Singingi Regency. To obtain activity data, an observation sheet is used which is filled in during the learning process and data on learning outcomes is obtained through a test sheet given at the end of the cycle. The increase in learning outcomes is seen from the number of students who complete at the end of the cycle. From the results of observations of teacher activity in cycle I, it seems that it has not been maximized because there are still some cryptocurrencies that have not been implemented, but in cycle II the teacher has carried out good guidance which has an impact on student activity also experiencing an increase for each meeting so that at the end of the cycle student learning outcomes have increased. than in the first cycle. In the first cycle only 10 students (56%) completed and in the second cycle there were 16 students (89%) who were declared complete according to the specified KKM. The increase in cycles I and II was 33% (6 students). From this data it can be concluded that the use of the Recitation method can increase student activity and learning outcomes. Â